Timing Matters: Comparing the Effects of Immediate, Delayed, and No Feedback on User Trust in Interactive Systems - Sena, Maria Klara Brito; Lima, Emilly Yorke Araújo; Paradeda, Raul Benites (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2025)
This study examines the impact of feedback timing on user trust and perceived reliability in interactive systems. Three scenarios were tested: no feedback, immediate feedback, and delayed feedback. Thirty participants interacted with these scenarios and completed trust-based questionnaires. Results show that immediate feedback significantly enhances user trust and perceived reliability, followed by delayed feedback, while the absence of feedback undermines these factors. The study aligns with human-computer interaction theories and extends recent research on user experiences. Findings emphasize the importance of implementing timely feedback in interactive system design, particularly immediate feedback when feasible. This research provides insights for improving user experience across various domains, including critical areas like healthcare technology. Future studies should address limitations in sample size and task diversity and explore different feedback modalities and user characteristics.